Chef Slowik’s Self-Entitlement in The Menu (2022) - Yoshua Veron Handika Putra Siadari; Rommel Utungga Pasopati; Kusuma Wijaya (PT. Padang Tekno Corp, 2025)
This paper examines the idea of narcissistic self-entitlement as portrayed by Chef Julian Slowik in Seth Reiss and Will Tracy’s The Menu. The study focuses on Chef Slowik’s excessive sense of self-importance and uses qualitative exploratory analysis to analyze how his actions indicate narcissistic behavior. The study examines situations in which Chef Slowik continuously prioritizes his own demands and desires over everyone else’s, even in the face of other people’s sadness and suffering. The study demonstrates how Chef Slowik’s behaviors affected other people’s emotional well-being by examining particular scenes in the film and highlighting his self-entitlement as an example of extreme narcissistic conduct. The analysis concludes that Chef Slowik’s self-entitlement is a powerful example of taking advantage of other people in order to further his own goals.